KETERAMPILAN PENGEMASAN MINUMAN TUAK MANIS (TUNIS) PADA KELOMPOK TANI LAJA DESA TOMPOBULU, KECAMATAN TOMPOBULU, KABUPATEN MAROS - St. Maryam; Muliadi; Amin, Kasma (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2024)
Community service activities have been held in Tompobulu Village, with the target partner namely the Laja Farmers Group located in Tompobulu Village, Tompobulu District, Maros Regency. This activity aims to package sweet palm wine as a fresh drink so that it can provide new income for farmer groups and community members in the village. Another goal is to preserve the palm tree plant because this plant is very much needed in human life and can also function as a protective tree for other plants, such as coffee, pepper, indigo, grapes, chili peppers. Nira trees grow abundantly in Tompobulu Village and the surrounding villages as one of the village's local treasures. The implementation method is training in packaging skills for sweet palm wine as a natural fresh drink in Tompobulu, Maros. This training consists of several stages, namely first the instructor's introduction to the farmer group members; secondly, introduction of packaging media; thirdly, Tunis beverage packaging; four procedures for packaging Tunis beverage bottles; five advantages of Tunis bottle packaging. This training involves members (women) of the Laja farmer group, especially farmers who produce palm wine. Through the activities of this farmer group, it is hoped that it will become a pilot project for packaging Tunis bottles as a fresh drink for the people of Tompobulu and/or can be used as a special snack for tourists because there are several tourist attractions in the area. The result of this activity is that the Laja farmer group can package their own palm wine in packaging and label it to mark it on the packaging. Apart from that, the farmers' level of understanding can be assessed from the results of the pre and post tests carried out, where their understanding increases by implementing good and clean processing, packaging and labeling methods. Farmers can increase their income, one of the ways is by selling this product in clean and healthy packaging. What can be concluded is that the farmers have skills in packaging Tunis after receiving training and can increase the economic value of the palm wine farming community.